CHILD [AND] ACCOUNTING - Krisno Septyan (Veteran Economics, Management, & Accounting Review, 2023)
children and love, they have been on the fringes of the accounting discussion, they are not logocentric accounting,a pitty. Keywords: child; accounting; solipsism